Linguistic Representation of Women: A Study of Eight Varieties of Women's Language in Little Women Movie - Maemuna Muhayyang; Muh.Fakhrul Armas; Syamsiarna Nappu (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Language not only reflects but also shapes societal roles, and in Little Women, the way women express themselves through language offers a powerful lens into their social realities. This study examines the linguistic representation of women using eight varieties of women’s language in the Little Women movie. The central problem of this research is to identify which features of women’s language are employed by the main female characters based on their social context. A qualitative descriptive approach was adopted, analysing data from the movie’s dialogues and its script. The analysis was grounded in Lakoff’s (1975) theory of women’s language features. The findings show that not all varieties of women’s language are employed by the main characters. Jo, the central character, utilized eight features, including lexical hedges (48.6%), empty adjectives (1.3%), intensifiers (8.5%), hypercorrect grammar (1%), rising intonation on declaratives (18.4%), and super polite forms (10.9%). Tag questions and precise color terms were not used. Furthermore, the use of these linguistic features is closely connected to the social conditions and gender roles in their society.